Relation of socioeconomic position to the case fatality, prognosis and treatment of myocardial infarction events; the FINMONICA MI Register Study. Issue 7 (1st July 2001) - Salomaa, V; Miettinen, H; Niemelä, M; Ketonen, M; Mähönen, M; Immonen-Räihä, P; Lehto, S; Vuorenmaa, T; Koskinen, S; Palomäki, P; Mustaniemi, H; Kaarsalo, E; et al.
Abstract : OBJECTIVE: To examine socioeconomic differences in case fatality and prognosis of myocardial infarction (MI) events, and to estimate the contributions of incidence and case fatality to socioeconomic differences in coronary heart disease (CHD) mortality. DESIGN: A population-based MI register study. METHODS: The FINMONICA MI Register recorded all MI events among persons aged 35–64 years in three areas of Finland during 1983–1992. A record linkage of the MI Register data with the files of Statistics Finland was performed to obtain information on socioeconomic indicators for each individual registered. First MI events (n=8427) were included in the analyses. MAIN RESULTS: The adjusted risk ratio of prehospital coronary death was 2.11 (95% CI 1.82, 2.46) among men and 1.68 (1.14, 2.48) among women with low income compared with those with high income. Even among persons hospitalised alive the risk of death during the next 12 months was markedly higher in the low income group than in the high income group. Case fatality explained 51% of the CHD mortality difference between the low and the high income groups among men and 38% among women. Incidence contributed 49% and 62%, respectively. CONCLUSIONS: Considerable socioeconomic differences were observed in the case fatality of first coronary events both before hospitalisation and among patients hospitalised alive. Case fatality explained a half of the CHD mortality difference between the low and the high income groups among men and more than a third among women.